Determination of condition factor (cf) and Hepatosomatic Index (hsi) of Pangasius sp. from Jeli market - Mohammad Amiruddin Ismail (2017)
Conditions factors (CF) and hepatosomatic index (HSI) of Pangasius sp. from Jeli market been studied for a period of three months (July-September 2016). The total length and weight of fish were recorded. The highest condition factor value is 1.05 while the lowest condition factor is 0.69. There are some factor contribute to the result such as availability of food organisms at a particular time and average temperature at the habitat. The result of this study indicates that the environment is not too suitable for the species. It also indicates that the understanding of local community in Jeli about this issue is still in low level. This study has contributed to the knowledge of fish populations in this economically important area that could assist fishery management scientists in carrying out future ecological studies in line with the strategies of conservation, restoration and management. Sustainable management of the species, however, requires that the environment be protected against anthropogenic pollution to enable the species to survive.